Design and application of a 5 step risk assessment tool for confined space entries. (December 2015) - Burlet-Vienney, Damien; Chinniah, Yuvin; Bahloul, Ali; Roberge, Brigitte
Highlights: Issues concerning risk assessment for confined space entries. Design of a tool based on risk management standards. Feedback from experts and organizations which manage confined space entries. Questionnaire for comprehensive risk identification. Criteria for categorizing interventions and rescue conditions. Abstract: Many serious accidents related to work in confined spaces still occur. Despite all the regulatory and standard-setting efforts that have been made, organizations seem to have difficulties with risk assessment for interventions in confined spaces. Risk identification and estimation were not carried out in most of fatal accidents. This paper proposes a 5 step risk assessment tool for confined spaces based on risk management standards. The tool was tested by 22 experts in managing entries in confined spaces, including experts during 10 visits in different organizations. Step 1 consists of a questionnaire to describe the configuration of the selected confined space, its environment and the work situations. The answers generate predefined types of risk such as mechanical, atmospheric, falling, chemical, and biological. Step 2 describes the components of risks (i.e., hazards, hazardous activity, hazardous event, harm). Step 3 estimates risk using adapted risk parameters and matrix. Step 4 categorizes the intervention by class and level of risk. Step 5 is a feedback loop for estimating residual risks after risk reduction measures have been taken. This tool enables to (i) carry out comprehensive risk identification by analyzing all the risk factors during an intervention in a confined space, (ii) categorize interventions and rescue conditions by using specific criteria, (iii) determine if two situations are indeed identical in terms of risks, (iv) decide if intervention planned meets the permit required confined spaces definition, (v) evaluate if external rescue is feasible, and (iv) decide if the residual risks are acceptable.